Prescribing Patterns and Variations of Antibiotic Use for Children in Ambulatory Care: A Nationwide Study - Githa Fungie Galistiani; Ria Benkő; Balázs Babarczy; Renáta Papp; Ágnes Hajdu; Éva Henrietta Szabó; Réka Viola; Erika Papfalvi; Ádám Visnyovszki; Mária Matuz (MDPI AG, 2022)
The aim of this study was to analyse characteristics of paediatric antibiotic use in ambulatory care in Hungary. Data on antibiotics for systemic use dispensed to children (0-19 years) were retrieved from the National Health Insurance Fund. Prescribers were categorised by age and specialty. Antibiotic use was expressed as the number of prescriptions/100 children/year or month. For quality assessment, the broad per narrow (B/N) ratio was calculated as defined by the European Surveillance of Antimicrobial Consumption (ESAC) network. Paediatric antibiotic exposure was 108.28 antibiotic prescriptions/100 children/year and was the highest in the age group 0-4 years. Sex differences had heterogenous patterns across age groups. The majority of prescriptions were issued by primary care paediatricians (PCP). The use of broad-spectrum agents dominated, co-amoxiclav alone being responsible for almost one-third of paediatric antibiotic use. Elderly physicians tended to prescribe less broad-spectrum agents. Seasonal variation was found to be substantial: antibiotic prescribing peaked in January with 16.6 prescriptions/100 children/month, while it was the lowest in July with 4 prescriptions/100 children/month. Regional variation was prominent with an increasing west to east gradient (max: 175.6, min: 63.8 prescriptions/100 children/year). The identified characteristics of paediatric antibiotic use suggest that prescribing practice should be improved.